Entre fraldas e letras, fazeres e afetos: enredos de educadoras infantis (UMEIs de Belo Horizonte /2007-2008) - Genicia Martins de Matos (2009)
This study examines educators who are the children of two units of Municipal Child Education (UMEIs) from Belo Horizonte, as we see and feel your work and working condition. Discussed, especially the routine work of educators with the children, especially the architecture of time, space and the practices that constitute it. It also has an initial analysis of their autoimagens professionals, their ideas on children, as well as the joys, tensions and difficulties included the day-to-day practitioners of the two UMEIs. Looking further, identify and understand the reasons and circumstances associated with entry and stay of educators in professional activity, seeking to interpret the meanings they attach to. The research was conducted with educators that serve children between 1 and 6 years old in 2007 and 2008. This is a qualitative perspective in research, carried out by direct observation of everyday life of educators in the combined UMEIs conducting interviews individual narratives and interviews with groups of semi-educators of these institutions. The professionals were divided into two groups according to age of children with which worked, well defined groups: educators who work with first cycle (children under three years) and those working with the second cycle (children over three years). Among the major findings of this study is the existence of common and different points revealed by these two segments of childhood educators on the issues investigated. They are close, for example, the reference that maintains its autoimagens professionals, ie what they consider to be a teacher or as a teaching. However, the educators working with children under three years, actions that require care (physical and emotional) very intense, consider that the image of teacher is not enough to define the complexity of doing such work. Another point that relates to them share their joy in this work therefore attach to the relationship with the children - in between diaper and letters, make and affection - feelings of joy, gratification and beauty. They participate, witness and work with the development of children. They enable children to learn and incorporation of cultural knowledge and practices, individually and collectively. The aspects which differentiate it, is that the professionals working with children under three years revealed that the physical care (health and nutrition), and prevail in protecting their routines of work, occupying much of their time to read daily with the child in the institution, undermining the achievement of other educational activities. As for educators of children over three years, have concerns regarding the conduct of activities for teaching reading and writing of letters and numerals, and the development of skills in children (cutting, pasting, listening and storytelling, among others). In this subgroup, the activities of care do not seem to be a significant point of tension and difficulty in daily routine. These are located, especially in the devaluation of the social and professional activity, associated to the imaginary part of a social and disqualifies it devalues the work women considered as a certain type of services and care as well as the children and work with them; and, secondly, is inferiorização and neglect of public education to the child, at the lowest level of the education system and are therefore less valued material and symbolic in social hierarchies and school, in public policy and management education.